Teaching communication skills in family medicine: A qualitative study - Rabaa K. Al-Momen; Saad M.Al-Battal; Adel M. Mishriky (Universiti Kebangsaan Malaysia, 2015)
Background:The ability of a doctor to communicate with patients effectively is one of the core competencies of a family physician. Teaching communication skills is a peculiar and challenging subject. Objectives:This study was conducted to explore the perceptions of family medicine trainers, their teaching approaches, and their opinions about improvements in teaching communication skills. Materials and Methods:The was a qualitative study. Both semi-structured interviews and a focus group discussion were used. The group of trainers was purposively selected and analysis was performed manually. Results:Twenty-four trainers were interviewed. It was found that interviewees perceived teaching communication skills as something very important and interesting but challenging and difficult. Effective teaching of the subject was limited by curriculum design where time distribution between the hospital and family medicine training did not satisfy the requirement of teaching communication skills. Time constraints and the organization of patient services in family medicine teaching centers contribute to the challenges of teaching the subject effectively. The practice of and the attitudes toward effective communication skills teaching methods were variably perceived among this group of trainers. The assessment modalities as a final point in the whole process of teaching were not perceived as a discriminating indicator to the true level of residents’ communication skills. Their main ideas for improvements were to give more emphasis to the teaching curriculum, to give it more weight in the final assessment of the board examination, and to establish standard teaching skills and attitudes toward the practice of communication skills in family medicine. Conclusions:Communication skills teaching in family medicine is a complex area of training. Focused efforts are required in developing the curriculum and training standards.